New taxa of Impatiens (Balsaminaceae) from Madagascar VII. Two new species of Impatiens from Mt. Marojejy, Madagascar - Fischer, Eberhard; Rahelivololona, Marie Elisette (Phytotaxa, 2015)
Two new species, Impatiens susan-nathansoniae and I. hendrikii, from Mt. Marojejy, Madagascar, are described. Impatiens susan-nathansoniae is related to I. humblotiana from eastern central Madagascar, but differs in the shape of the lower sepal with spur, the dorsal petal and the lateral united petals. Impatiens hendrikii is related to I. fuchsioides, but differs in the straight stem, the larger leaves, the broader lateral sepals, the broader lateral united petals with different shape, and the glabrous lower sepal gradually tapering into a short, saccate, whitish red spur.